A stochastic multi-scale model of HIV-1 transmission for decision-making: application to a MSM population. - Lilit Yeghiazarian (Public Library of Science (PLoS), 2013)
Background In the absence of an effective vaccine against HIV-1, the scientific community is presented with the challenge of developing alternative methods to curb its spread. Due to the complexity of the disease, however, our ability to predict the impact of various prevention and treatment strategies is limited. While ART has been widely accepted as the gold standard of modern care, its timing is debated. Objectives To evaluate the impact of medical interventions at the level of individuals on the spread of infection across the whole population. Specifically, we investigate the impact of ART initiation timing on HIV-1 spread in an MSM (Men who have Sex with Men) population. Design and methods A stochastic multi-scale model of HIV-1 transmission that integrates within a single framework the in-host cellular dynamics and their outcomes, patient health states, and sexual contact networks. The model captures disease state and progression within individuals, and allows for simulation of therapeutic strategies. Results Early ART initiation may substantially affect disease spread through a population. Conclusions Our model provides a multi-scale, systems-based approach to evaluate the broader implications of therapeutic strategies.